PORTOFOLIO OPTIMAL DENGAN METODE BEST BETA CAPM ( Studi Kasus Pada Saham â Saham LQ-45 Periode 2010 â 2013 ) - , ASTRIANI KUSUMANINGRUM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The issue of 'best-betaâ arises as soon as potential errors in the Sharpe- Lintner-Black capital asset pricing model (CAPM) are acknowledged. By incorporating a target variable into the investor preferences, this study derives a best-beta CAPM (BCAPM) that maintains the CAPM's theoretical appeal and analytical simplicity yet unambiguously improves its pricing accuracy. Empirical observations suggest that the BCAPM predicts expected returns better than the CAPM by 20% to 30% annually. Where we cannot invent, we may at least improve